Selective and Superselective Angiography of Pediatric Moyamoya Disease Angioarchitecture: The Anterior Circulation. Issue 4 (July 2014) - Baltsavias, Gerasimos; Valavanis, Anton; Filipce, Venko; Khan, Nadia
The angioarchitecture of the so-called moyamoya vessels in children has not been explicitly analyzed. We aimed to investigate the precise anatomy of the vascular anastomotic networks in patients with childhood moyamoya disease. Six children diagnosed with moyamoya disease for the first time underwent an angiographic investigation with selective and superselective injections. We recorded the arterial branches feeding the moyamoya anastomotic networks, their connections and the recipient vessels. Depending on the level of the steno-occlusive lesion, the feeding vessels included the medial striate arteries, the perforators of the choroidal segment of the carotid, the uncal artery, the medial and lateral branches of the intraventricular segment of the anterior choroidal artery, perforators of the communicating segment, the superior hypophyseal arteries, the prechiasmal branches of the ophthalmic artery, the ethmoidal arteries and the dural branches of the cavernous carotid. Through connections, which are described, the recipient vessels were the lateral striate arteries and the middle cerebral, the medial striate arteries and the anterior cerebral, medullary arteries around the ventricular system, anterior temporal branches of the middle cerebral, orbitofrontal and frontopolar branches of the anterior cerebral, as well as other cortical branches of the anterior and middle cerebral territories. The use of high quality selective and superselective angiography enabled us to clearly demonstrate for the first time aspects of the microangiographic anatomy of the moyamoya anastomotic network previously only vaguely or incompletely described.